2015
DOI: 10.1007/s10549-015-3590-1
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome and acute myeloid leukemia following adjuvant chemotherapy with and without granulocyte colony-stimulating factors for breast cancer

Abstract: Purpose Risk of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) post-breast cancer treatment with adjuvant chemotherapy and granulocyte colony-stimulating factors (G-CSF) is not fully characterized. Our objective was to estimate MDS/AML risk associated with specific breast cancer treatments. Methods We conducted a retrospective cohort study of women ages ≥66 years with stage I-III breast cancer between 2001 and 2009 using the Surveillance, Epidemiology and End Results-Medicare database. Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Few large epidemiological studies have investigated the association between receipt of G‐CSF and the risk of MDS/AML among elderly patients with NHL, although leukemogenesis associated with G‐CSF has been suggested in studies of other cancer sites, such as breast cancer . In a study using the SEER‐Medicare–linked database by Gruschkus et al, patients who had NHL diagnosed between 1992 and 2002 and received chemotherapy had a 5‐year cumulative risk of MDS/AML of approximately 7% if they received G‐CSF, compared with approximately 4% if they did not receive it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few large epidemiological studies have investigated the association between receipt of G‐CSF and the risk of MDS/AML among elderly patients with NHL, although leukemogenesis associated with G‐CSF has been suggested in studies of other cancer sites, such as breast cancer . In a study using the SEER‐Medicare–linked database by Gruschkus et al, patients who had NHL diagnosed between 1992 and 2002 and received chemotherapy had a 5‐year cumulative risk of MDS/AML of approximately 7% if they received G‐CSF, compared with approximately 4% if they did not receive it.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed neither an association between pegfilgrastim and MDS/AML risk nor a trend toward an increased risk with greater number of pegfilgrastim doses. Another study of older patients with breast cancer who were identified in the SEER‐Medicare–linked database between 2001 and 2009 reported an increased risk of MDS/AML that was exclusive to filgrastim and was not observed with pegfilgrastim . The risk associated with filgrastim was highest among women who received treatment with an anthracycline‐based chemotherapy regimen for breast cancer (HR, 2.11; 95% CI, 1.29‐3.30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of factors that may contribute to the risk of developing MDS/AML concurrent with PARPi treatment, but it is important to keep in mind that the overall risk is quite low. Treatment with chemotherapy has also been shown to increase the risk of developing MDS/AML [78]. Most patients who participated in PARPi clinical studies were heavily pre-treated with chemotherapy, with some patients receiving three or more lines of chemotherapy prior to PARPi treatment [49,50,52,54].…”
Section: Potential Parpi Toxicities and Management Strategiesmentioning
confidence: 99%
“…1,2 Chemotherapy reduces the risk of disease recurrence and improves survival. 3 Nevertheless, it is associated with risks of adverse events and toxicities, [4][5][6] particularly among low-risk patients, 7 leading to increased healthcare expenditures and reduced health-related quality of life 8 that may outweigh its benefits.…”
Section: Introductionmentioning
confidence: 99%